PENGEMBANGAN MODUL PEMBELAJARAN DESAIN WEB MENGGUNAKAN PROGRAM ARTISTEER PADA PRODI TKJ POLITEKNIK JAMBI - -, Darmuji -; Murbojono, Rahmat -; M, Damris - (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
The purpose of this research is to develop Web Design Learning module by using Artisteer Program to facilitate students in learning Web Design. The module is developed applying Dick and Careyâ€™s model. The result reveals that the moduleÂ is easy to use as a learning module.Â It is suggested that before developing a learning module, there should be done need analysis to assure that the developed product can be utilised optimally. For the further development, it is suggested to produce a module with artisteer program 2.50 version accompanied with tutorial CD. Keywords: learning module, web design, artisteer program